Onion (Allium cepa) DNA extraction: Perspective of scientific practices through laboratory practice (Research, Society and Development, 2023)
DNA represents the structural unit of life, being one of the best-known organic substances. DNA extraction has become a alternative to teaching-learning in Biology classes. In this sense, the objective of this work was to facilitate the learning of high school Biology students, based on an experimental activity involving the extraction of DNA from onions (Allium cepa). The activity was implemented in a practical class laboratory at IFPE-Campus Barreiros in two pedagogical moments. The first moment consisted of a practical class for extracting DNA from A. cepa, using everyday materials. In the second moment, students were invited to evaluate the activity through a questionnaire. From the analysis of the results, it was possible to verify that the proposed activity encouraged motivation, aroused curiosity and facilitated students learning. Furthermore, the evaluation of the activity by the students was considered stimulating by the authors. Finally, in addition to combining theory with practice, this work can be useful as reference material on the DNA molecule.